201 Management of an unusual presentation of spontaneous intracranial hypotension (SIH). Issue 6 (27th May 2022) - Mohideen, Muhammed; Benger, Matthew; Mahmood, Amira; Hoffman, Jan; Goadsby, Peter; Stanton, Biba; Carlton-Jones, Lalani
Abstract : A 49-year-old woman presented with 9 months of progressive cognitive decline and somnolence. In the last few weeks she developed right hand tremor, unsteadiness and urinary incontinence, which improved after lying flat. There was no headache. Examination findings included vertical gaze restriction, hypomimia, right-sided rest tremor, rigidity and bradykinesia, globally brisk reflexes and an unsteady gait. She scored 50/100 on the Addenbrooke's Cognitive Examination. Brain MRI showed features consistent with intracranial hypotension with marked 'brain sag' but standard imaging did not identify the site of the leak. Two blind blood patches were followed by only transient symptomatic improvement. Initial Digital Subtraction Myelogram (DSM) was non-diagnostic, but repeat DSM identified a leak at C6–7 with an irregular diverticulum/CSF-venous fistula. A CT-guided fibrin patch injected at C6/7 resulted in transient improvement. Finally, a neurosurgical procedure was performed to coagulate the venous plexus adjacent to the C7 nerve root. This effected a dramatic and sustained improvement in her cognitive and motor symptoms. SIH is a treatable cause of cognitive decline and parkinsonism. DSM is a novel approach to localising CSF leaks. This is the first reported cognitive presentation of SIH where identification of a CSF leak with DSM led to successful surgical treatment. saamir.mohideen@nhs.net